LEADERSHIP OF SCHOOL PRINCIPLE IN DEVELOPING EDUCATION MANAGEMENT STANDARDS AT MTS YASPIDA SUKABUMI - Hanafiah; Muhammad Firman; Uce Gunawan (Lembaga Pengembangan Pembelajaran Penelitian dan Pengabdian Masyarakat Universitas PGRI Mahadewa Indonesia, 2023)
This research discusses the role of school principals' leadership in the development of education management standards at MTs Yaspida Sukabumi. The aim of this research is to improve the education quality through the implementation of effective management standards. The research method used is qualitative, involving the school principal, teachers, and students as respondents. Data were collected through interviews, observations, and documentation. The results of the research indicate that the leadership of the school principal plays a significant role in developing education management standards. School principal who has a clear vision, good communication, inclusive leadership, and the ability to mobilize the entire school community can create an conducive environment to improving the education quality. This research concludes that effective school leadership in the development of management standards have a positive impact on the education quality at MTs Yaspida Sukabumi.